Analisis Kepercayaan dan Niat Perilaku Konsumen dalam Menggunakan QRIS Guna Mendorong Pengembangan UMKM di Kota Surakarta - Rifai Apriture Afianto; Mirzam Arqy Ahmadi (Universitas 45 Surabaya, 2025)
The development of digital payment technology, particularly QRIS, facilitates cashless transactions and is expected to promote the growth of Micro, Small, and Medium Enterprises (MSMEs) by simplifying transactions between consumers and business owners. Surakarta was chosen as the research location due to its relatively low number of QRIS users, despite the significant potential to increase the adoption of digital payment systems. The study involved 105 respondents. The analysis results show that Mobile Usability significantly affects Interest, Attitude, and Intention (p < 0.05), while Trust does not significantly affect Interest but does influence Attitude and Intention. Attitude and Intention were found to significantly affect Interest. The model used has an R² value of 0.286 for Interest and 0.419 for Attitude and Intention, indicating that the model effectively explains the relationship between the independent and dependent variables. This study has limitations, including a small sample size and constructs that lack convergent validity, which need to be addressed in future research. The findings provide valuable insights into the impact of QRIS usage and trust on consumer attitudes and intentions in adopting digital financial technology, which is expected to support the development of MSMEs and the digital transformation in Surakarta.